The Electro-Excitation Form Factors of 7Li Nucleus with Exact Center of Mass Correction - Al-qazaz, B. S. (Iraqi Journal of Physics, 2010)
The inelastic longitudinal electron scattering form factors are calculated for the low-lying excited states of 7Li the first excited state 2121TJ (0.478 MeV) and the second excited state 2127TJ (4.63 MeV). The exact value of the center of mass correction in the translation invariant shell model (TISM) has been included and gives good results. A higher 2p-shell configuration enhances the form factors for high q-values and resolves many discrepancies with the experiments. The data are well described when the core polarization (CP) effects are included through effective nucleon charge. The results are compared with other theoretical models. Keyword: 7Li inelastic electron scattering form factors calculated with exact center of mass correction. CP is included through effective charge model